Laparoscopic partial splenectomy for a splenic hamartoma - Vashisht Madabhushi; Timothy Horrell; John M. Draus, Jr (Elsevier, 2021)
Objective: We discuss current knowledge and management of splenic hamartoma, an uncommon form of benign tumor. Summary background data: A splenic hamartoma is a rare form of benign splenic mass, often found incidentally while working up other complaints, and is typically treated by surgical resection of the mass. In this case, we discuss the management of an incidentally found splenic hamartoma that was treated with laparoscopic partial splenectomy. Methods: The patient presented in the Emergency Department complaining of periumbilical pain after having been struck in the abdomen with a soccer ball the previous day. Following a physical exam and blood work, an ultrasound was performed that revealed a hypoechoic area within the spleen. The patient received a diagnosis of gastroenteritis and an appointment for follow-up at 2 months. At 2-month follow-up, an ultrasound indicated that the mass had grown. The mass appeared consistent with a splenic hemangioma, so the patient was scheduled for laparoscopic partial splenectomy. Results: The mass was completely resected without any complications. The patient had an uncomplicated postoperative course. Conclusions: When there are no other indications for a total splenectomy and malignancy is unlikely, laparoscopic partial splenectomy appears to be a reasonable treatment modality for a splenic hamartoma.